Incoming Students' readiness for interprofessional learning from 2020 onwards - Quach, Shirley; Oliveira, Ana; Elzibak, Ohood; Malott, Anna; Hamilton, Justine; Patterson, Sarah; Mohaupt, Jennifer; Nash, Jennifer; Harris, Jocelyn; Gregor, Sarah; Akhtar-Danesh, Noori; Bondy, Linda; et al. (My University, 2022)
Background: Due to the COVID-19 pandemic, post-secondary programs transitioned from in-person learning to virtual hybrid formats to meet contact restrictions. Although virtual options increased accessibility and convenience,1 healthcare programs were challenged by the restrictive delivery method that had to meet the needs of students and curriculum standards.2 Interprofessional education (IPE) is an important component for students in professional health programs to experience. Emerging research shows students are aware of the relevance of interprofessional practices and their value in healthcare.1,3 However, there is limited evidence to describe how receptive students are towards virtual IPE. Objective: The study objective is to report IPE readiness in students entering the Faculty of Health Sciences (FHS) during the COVID-19 pandemic from 2020 to 2022. Method: Students entering the FHS at McMaster University were invited to participate in this survey. Disciplines invited were from undergraduate general (Health Sciences) and professional programs (Physician Assistant, Nursing, Medicine, Midwifery, Social Work) and graduate professional programs (Speech Language Pathology, Physiotherapy, Occupational therapy, Child Life). The Readiness for Interprofessional Learning Scale (RIPLS) was used to collect students’ feedback toward IPE. Incoming students were randomly invited to complete RIPLS using a 5-point Likert scale or Q-sort table within the first month of their studies. Results: Over 3 years, 3944 students were invited, and 1298 (33%) students responded to the survey. In total, 1074 students completed RIPLS with the 5-point scale (n=582 in 2020; n=324 in 2021; n=168 in 2022) and 224 students completed RIPLS with Q-sort tables (n=109 in 2020; n=71 in 2021; n=44 in 2022). Students from all disciplines responded. The mean age for students answering the Likert version was 21.71 years (SD 4.5) and for Q-sort was 21.72 years (SD 4.38). Conclusions: Students’ responses and subjective feedback on the roles and responsibilities, professional identities, and collaboration for interprofessional work will be discussed.
Incoming Students' Readiness for Interprofessional Learning from 2020 onwards presented on December 5, 2022 at McMaster University, Hamilton, Ontario, Canada.
Keywords: Interprofessional Education; Covid-19 Pandemic; Health Sciences; Q-sort method; Likert scale